Предмет:
МатематикаАвтор:
анонимf(x)\' = (-√x)’ = (-1 * √x)’ = (-1) * (√x)’ = (-1) * (1 / 2√x) = -1 / 2√x.
f(x)\' = ((x^3 + 1)^4)’ = (x^3 + 1)’ * ((x^3 + 1)^4)’ = ((x^3)’ + (1)’) * ((x^3 + 1)^4)’ = (3x^2 + 0) * 4 * (x^3 + 1)^3 = 12x^2 * (x^3 + 1)^3.
f(x)\' = ((x^2 + 1) / (x^2 – 1))’ = ((x^2 + 1)’ * (x^2 – 1) - (x^2 + 1) * (x^2 – 1)’) / (x^2 – 1)^2.
f(x)\' = (4x^2 + 6x + 3)’ = (4x^2)’ + (6x)’ + (3)’ = 4 * 2 * x + 6 + 0 = 8x + 6.
x)\' = ((5x + 1)^(-3))’ = (5x + 1)’ * ((5x + 1)^(-3))’ = ((5x)’ + (1)’) * ((5x + 1)^(-3))’ = (5 + 0) * (-3) * (5x + 1)^(-4) = -15 * (5x + 1)^(-4) = -15 / (5x + 1)^4.
Автор:
blackburnДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть